1999
DOI: 10.1086/315033
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Three DistinctCryptosporidium parvumIsolates for Healthy Adults

Abstract: The infectivity of three Cryptosporidium parvum isolates (Iowa [calf], UCP [calf], and TAMU [horse]) of the C genotype was investigated in healthy adults. After exposure, volunteers recorded the number and form of stools passed and symptoms experienced. Oocyst excretion was assessed by immunofluorescence. The ID50 differed among isolates: Iowa, 87 (SE, 19; 95% confidence interval [CI], 48.67-126); UCP, 1042 (SE, 1000; 95% CI, 0-3004); and TAMU, 9 oocysts (SE, 2.34; 95% CI, 4.46-13.65); TAMU versus Iowa, P=.002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
236
0
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(253 citation statements)
references
References 44 publications
8
236
0
9
Order By: Relevance
“…Table 1 show that the prevalence of Cryptosporidium spp. in the present study (57%) was close to 52.2% reported by Hasan et al (2010) in Iraq and to others reported by many researchers in different countries: 59% in USA (Okhuysen, et al, 1999), 55% in Czech Republic (Kvac and Vitovec, 2003), 54.5% in Tanzania (Swai and Schoonman, 2010), and 56% in Myanmar (Bawm et al, 2014). The high estimation of prevalence of Cryptosporidium spp.…”
Section: Discussionsupporting
confidence: 89%
“…Table 1 show that the prevalence of Cryptosporidium spp. in the present study (57%) was close to 52.2% reported by Hasan et al (2010) in Iraq and to others reported by many researchers in different countries: 59% in USA (Okhuysen, et al, 1999), 55% in Czech Republic (Kvac and Vitovec, 2003), 54.5% in Tanzania (Swai and Schoonman, 2010), and 56% in Myanmar (Bawm et al, 2014). The high estimation of prevalence of Cryptosporidium spp.…”
Section: Discussionsupporting
confidence: 89%
“…[30][31][32][33] Increased numbers of cases of C. parvum infection in Fortaleza and Lusaka during the rainy season were associated with contaminated drinking water supplied to these population, 3,6 but source of drinking water and mode of water disinfection were not associated with the odds of C. parvum infection among our study population. Because the 50% infectious dose is relatively low for C. parvum, ranging from approximately 10 to 1,000 for healthy humans, 34 oocysts could be transmitted through low levels of contaminated water or food, followed by person-to-person transmission, especially among household members. Food-borne C. parvum infection has been transmitted through ingestion of freshpressed apple cider, and risk factors for food-borne transmission have had been reported for consumption of stored cooked food, fresh sausages, offal, and raw milk.…”
Section: Discussionmentioning
confidence: 99%
“…Human disease has been traditionally attributed to Cryptosporidium parvum but it was apparent from both the early epidemiological questions raised regarding the zoonotic status and transmission of the organism that variants occurred. Animal infectivity studies in the 1980s demonstrated that infective dose sizes and clinical responses varied between isolates (Fayer & Ungar, 1986;Pozio et al, 1992) and human infectivity studies have demonstrated differences in ID 50, attack rate, pre-patent period, duration of disease, and frequency of stools between three different C. parvum isolates (IOWA, TAMU and UCP) (Okhuysen et al, 1999). Phenotypic analysis focussing on protein, antigenic and isoenzyme diversity showed that differences were consistent with other biological and/or epidemiological data and "animal types" and "human types" were suggested by McDonald and Awad-el-Kariem in 1995.…”
Section: Th Emop August 2008mentioning
confidence: 99%